"Do No Harm": Promoting Anti-Racist Policing in Pediatric Emergency Departments Through 20 Practice Change Considerations. Issue 3 (May 2023) - Wells, Jordee M.; Walker, Valencia P.
Children represent some of the most vulnerable and most valuable members of society. When acutely ill or injured, pediatric emergency departments (EDs) provide first line, specialized care for children and adolescents. Unique and unpredictable, the pediatric ED environment requires a wide range of health care professionals to care for children and their families and often includes hospital-employed security professionals and local law enforcement personnel to ensure safe and protective spaces paramount for optimal patient care. However, an active policing presence within environments designed to promote healing can paradoxically contribute to harm, particularly for Black and Brown patients. As health care systems pledge to dismantle structural racism and achieve health equity, efforts must include anti-racist reforms of threat management systems within clinical environments. We propose assessment and evaluation of current security and police encounters within pediatric EDs. We call for institution of policies that mitigate biases, address medical mistrust, distinguish clinical from criminal aggression, and minimize punitive contact with police. We outline a multitiered, patient-centered approach to disruptive and violent acts that prioritizes prevention, early intervention, and de-escalation strategies with a goal of reducing the perceived need for policing presence in pediatric EDs.